Prarancangan Pabrik Polistirena Dengan Proses Polimerisasi Larutan Kapasitas 75.000 Ton/Tahun - Nurhayati, Nurhayati, Ir. Haryanto, A.R., M.S, M. Mujiburohman, S.T., M.T., Ph.D (2016)
Polystyrene is widely used as raw materials in the cable industry, bottles, pipes, furniture and other products made of plastic. Polystyrene factory is expected to meet domestic demand and reduce the amount of imports from other countries. The factory is planned to operate for 330 days/year with a production capacity of 75.000 tons/year. The main raw materials required are styrene monomer 106,714.2860 tons/year ethyl benzene 6289.3200 tons/year and benzoyl peroxide 93.5855 tons/year. Location olystyrene plant is planned to be established in Cilegon, Banten in 2019. The need for water in the plant is derived from the river Cidanau while the electrical energy needs obtained from the PLN and generator. The process of making polystyrene is done by solution polymerization method. The manufacturing process is by reacting styrene monomer with the initiator benzoyl peroxide in a stirred tank reactor flow (RATB) equipped with a cooling jacket and takes place at 1 atm pressure conditions and a temperature of 90°C. Next, use a flash drum to separate vertical form vapor and liquid phase of the reactor output. Polystyrene product that comes out as a result of lower flash drum incorporated into the extruder to form a molten polystyrene into a pellet-shaped polystyrene measuring 1/8 in; whereas, the product on flash drum will be reused as recycle feed. The results of economic analysis of the plant design polystyrene showed that the total investment (Total Capital Investment) of Rp478.529.711.199 and total costs of production (Production Cost) Rp1.776.680.105.595. From feasibility analysis results obtained ROI (Return on Investment) before tax after tax 38.88% and 29.16%. POT (Pay Out Time) before tax after tax of 2.05 years and 2.55 years, BEP (Break Even Point) 44.30%, SDP (Shut Down Point) 25.68% and DCF (Discounted Cash Flow) of 30.51%. Based on consideration of the results of the analysis, it polystyrene plant with a capacity of 75.000 tons/year of this deserves to be studied further.